The potential carbon dioxide emissions reduction when energy service interventions are applied to the current subsidised housing demand - Krog, Petrus Jacobus (Energy Research Centre, 2017)
This dissertation examines the role of subsidised housing in reducing carbon dioxide (CO₂) emissions in South Africa. Climate change is an occurring event and is largely caused by human activities, such as the production of energy from fossil fuels (NRC, 2010). Buildings are seen as one of the highest consuming sectors of energy and therefore present many potential climate change mitigation opportunities. The South African subsidised housing sector is expanding significantly and estimations made in the current study show that 2.8 million subsidised housing units can potentially reduce up to 3% of the total current CO₂ emissions from the residential sector. This demand for subsidised housing units can also potentially reduce up to 0.06% of South Africa's total annual CO₂ emissions.